Psychological Profile in Children and Adolescents with Severe Course Juvenile Idiopathic Arthritis - Emanuela Russo; E. Trevisi; F. Zulian; M. A. Battaglia; D. Viel; D. Facchin; A. Chiusso; A. Martinuzzi (The Scientific World Journal)
Objective. Juvenile Idiopathic Arthritis (JIA) is the most common chronic pediatric rheumatic disease. It is recognized that only reliance on clinical signs of disease outcome is inadequate for understanding the impact of illness and its treatment on child’s life and functioning. There is a need for a multidisciplinary and holistic approach to children with arthritis which considers both physical and emotional functioning. This study investigated the psychosocial functioning of children and adolescent with JIA and the disease-related changes in their family. Methods. The sample consisted of 33 hospitalized patients, aged 6–16 years. Both parents and the children were given a number of questionnaire to fill out. Clinical information was extracted from the interviews. Results. Self-reported psychological functioning (depression, anxiety, and behavior) was not different from the normal population; however significant psychological suffering was detected by the clinical interview. Conclusions. Children and adolescents with JIA do not show overt psychopathology by structured assessment; nevertheless a more clinically oriented holistic approach confirms JIA as a disrupting event causing relevant changes in the quality of life of the affected families.